Implementation Of The Convention On International Trade In Endangered Species Of Wild Fauna And Flora (Cites) In Indonesia Related To Protected Wildlife Trade Cases - Lestari, Nisa; Sulaiman, Abdullah; Vience (Ridwan Institute, 2025)
Indonesia is one of the countries that has ratified the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), which serves as the main international instrument regulating trade in endangered animals and plants. As a consequence of this ratification, Indonesia is legally obligated to harmonize its domestic legal framework—currently embodied in Law Number 32 of 2024 concerning Amendments to Law Number 5 of 1990 on the Conservation of Biological Natural Resources and Their Ecosystems—with the principles of animal protection outlined under CITES. This article examines the implementation of CITES in Indonesia, particularly in the context of protected wildlife trafficking cases. It aims to identify the challenges faced in law enforcement and to propose policy recommendations that could strengthen national efforts in biodiversity protection. The research employs literature review, regulatory analysis, and case study methods to provide a comprehensive understanding of how CITES obligations are operationalized within Indonesia’s legal and institutional framework. Findings reveal that, despite the existence of an adequate legal foundation, operational barriers, weak inter-agency coordination, limited forensic capacity, and socio-economic pressures have undermined the overall effectiveness of CITES implementation. Therefore, this study recommends enhancing law enforcement capacity, regulatory harmonization, international collaboration, and public education campaigns to achieve more effective biodiversity conservation outcomes.